2019
DOI: 10.3892/etm.2019.7603
|View full text |Cite|
|
Sign up to set email alerts
|

Reduced miR‑202 levels enhanced oral cancer development via targeting Sp1

Abstract: The current study aimed to evaluate the possible role of microRNA (miR)-202 in the development of oral cancer. First, miR-202 levels were found to be decreased in the serum and tissues of oral cancer patients compared with healthy controls. Receiver operating characteristic analysis was carried out to explore the diagnostic value of serum miR-202 for oral cancer. Overexpression of miR-202 significantly decreased the migratory capacity of SCC-9 cells, while inhibition of miR-202 markedly increased the migratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…In previous studies, miR-202 also was found to be aberrantly expressed in endometrial tissues from patients with EMS ( 13 , 38 ). In addition, miR-202 has been previous shown to exert suppressive roles on the invasive and migratory capacities of tumor cells ( 43 - 45 ). According to the aforementioned findings from the present and previous studies, it could be hypothesized that miR-202 can regulate EMS progression.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, miR-202 also was found to be aberrantly expressed in endometrial tissues from patients with EMS ( 13 , 38 ). In addition, miR-202 has been previous shown to exert suppressive roles on the invasive and migratory capacities of tumor cells ( 43 - 45 ). According to the aforementioned findings from the present and previous studies, it could be hypothesized that miR-202 can regulate EMS progression.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in early-stage BC patients, a gradual decrease in miR-202 blood expression level was found to correlate with progression from early stage to tumor-node-metastasis (TNM) stage [ 11 ]. Similarly, a study on oral cancer reported decreased miR-202 levels in patient sera and cancer tissues [ 12 ].…”
Section: Circulating Mir-202 As a Diagnostic Biomarker In Cancer Pati...mentioning
confidence: 99%
“…Numerous clinical studies have addressed the role of miR-202 in gastrointestinal tract tumors (GIT), including oral [ 12 ], esophageal [ 19 , 20 , 21 ], gastric [ 22 , 23 , 24 ], pancreatic [ 25 , 26 , 27 , 28 ], hepatocellular [ 29 , 30 , 31 ], and colorectal [ 32 , 33 , 34 , 35 ] cancers, and documented a lower expression of miR-202 in tumor tissues and a tumor suppressive function of miR-202 overexpression on GIT cancer progression. In oral cancer cell lines, overexpression of miR-202 downregulated the protein expression level of the transcription factor Sp1, which, in turn, reduced cancer cell migration and invasion.…”
Section: Mir-202 As a Novel Gastrointestinal Tract Tumor Suppressormentioning
confidence: 99%
“…Overexpression of SP1 has been observed in HNSCC as compared to normal oral mucosa, and its inhibition downregulates growth in oral cancer cell lines ( Shin et al, 2013 ). SP1 serves as a therapeutic target against oral cancer ( Shin et al, 2012 ; Yu et al, 2013 ; Chae et al, 2014 ; Sun et al, 2016 ; Zhang et al, 2019 ; Zhao et al, 2019 ; Gao et al, 2020 ; Liu et al, 2020 ). SP1 is a functional target of miR-24.…”
Section: Role Of Hpv-related Transcription Factors In Handn Carcinogenementioning
confidence: 99%